Regulation of Nuclear Receptor Interacting Protein 1 (NRIP1) Gene Expression in Response to Weight Loss and Exercise in Humans. Issue 8 (28th June 2017) - De Marinis, Yang; Sun, Jiangming; Bompada, Pradeep; Domènech Omella, Judit; Luan, Cheng; Halu, Arda; Renström, Erik; Sharma, Amitabh; Ridderstråle, Martin
Abstract : Objective: Nuclear receptor interacting protein 1 (NRIP1) is an important energy regulator, but few studies have addressed its role in humans. This study investigated adipose tissue and skeletal muscle NRIP1 gene expression and serum levels in response to weight loss and exercise in humans. Methods: NRIP1 expression was measured by microarray and serum NRIP1 by ELISA and Western blotting. Skeletal muscle transcriptomes were analyzed from Gene Expression Omnibus databases. Network‐based proximity analysis was performed on the proximity of NRIP1 interacting genes in the human interactome. Results: In patients with obesity, adipose tissue NRIP1 mRNA expression increased during weight loss and weight maintenance and showed strong associations with metabolic markers and anthropometric parameters. Serum NRIP1 protein levels also increased after weight loss. In skeletal muscle, imposed rest increased NRIP1 expression by 80%, and strength training increased expression by ∼25% compared to baseline. Following rest, NRIP1 expression became sensitive to insulin stimulation. After re‐training, NRIP1 expression decreased. Interactome analysis showed significant proximity of NRIP1 interacting partners to the obesity network/module. Conclusions: NRIP1 gene expression and serum levels are strongly associated with metabolic states such as obesity, weight loss, different types of exercise, and peripheral tissue insulin resistance, potentially as a mediator of sedentary effects.